2008
DOI: 10.1254/jphs.fp0071400
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of T-2328, 2-Fluoro-4'-methoxy-3'-[[[(2S,3S)-2-phenyl-3-piperidinyl]amino]methyl]-[1,1'-biphenyl]-4-carbonitrile Dihydrochloride, as a Brain-Penetrating Antagonist of Tachykinin NK1 Receptor

Abstract: Abstract. The pharmacological properties of T-2328 were evaluated as an antagonist of the tachykinin neurokinin 1 (NK 1 ) receptor. T-2328 inhibited the specific binding of [ 3 H][Sar 9 ,Met(O 2 ) 11 ]substance P to tachykinin NK 1 receptors in human lymphoblastic IM9 cells with K i of 0.08 nM. In the same assay, K i for aprepitant, a brain-penetrating NK 1 antagonist, was 1.3 nM. The antagonism of T-2328 is highly selective for the human NK 1 receptors since the affinities for human NK 2 , NK 3 receptors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Emend was prepared by dissolving the drug in saline, with the vehicle control animals administered saline only. The dose of Emend was determined from previous studies, which have demonstrated this administration exerts central effects [17]. The dexamethasone dosage has been successfully used previously to treat experimental brain tumor associated edema [18].…”
Section: Methodsmentioning
confidence: 99%
“…Emend was prepared by dissolving the drug in saline, with the vehicle control animals administered saline only. The dose of Emend was determined from previous studies, which have demonstrated this administration exerts central effects [17]. The dexamethasone dosage has been successfully used previously to treat experimental brain tumor associated edema [18].…”
Section: Methodsmentioning
confidence: 99%
“…Aprepitant 8 (Emend, Figure 2C) was the first drug available on the market for the treatment of vomiting and nausea caused by chemotherapy regimen [29]. It exerts its action by blocking the neuro- Polyfluorinated groups in medicinal chemistry Review kinin-1 (NK-1) receptor.…”
Section: Aprepitantmentioning
confidence: 99%
“…CINV can be classified as acute phase (0–24 hours after chemotherapy) or delayed phase (24–120 hours after chemotherapy) based on the time of incidence. Neurokinin‐1 receptor antagonists (NK‐1RAs), a novel class of antiemetic medications including aprepitant, casopitant, fosaprepitant, netupitant, rolapitant, and others, play an efficient role in both acute and delayed CINV control by blocking the binding of substance P to the NK‐1R in the vomiting center of the central nervous system . Recently, a large‐scale network meta‐analysis has further confirmed that different NK‐1RAs‐based triple regimens (NK‐1RAs + serotonin receptor antagonist [5‐HT 3 RA] + corticosteroids) shared equivalent effect on CINV control in all the phases.…”
Section: Introductionmentioning
confidence: 99%